THE INFLUENCE OF DIGITAL MARKETING, ELECTRONIC WORD OF MOUTH (E- WOM), AND LIFESTYLE ON THE PURCHASE DECISION OF AERO STREET SHOE PRODUCTS - Taufik, Taufik; Pawestri Winahyu; Achmad Hasan Hafidzi (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to find out the factors that affect Aero street shoe users in making purchase decisions. Method: The population in this study is unknown due to the lack of certainty about the number of Aero street shoe users in the horseshoe area. The sampling technique used was purposive sampling, with a sample of 102 respondents. The data collection method used is a questionnaire. Results: Based on the results of the study, it can be concluded that digital marketing, electronic word of mouth, and lifestyle partially have a positive and significant effect on purchase decisions. Novelty: The results of the study can be used to build an online marketing strategy to have a high impact in increasing consumer response by using a three-variable approach (digital marketing, electronic word of mouth, and lifestyle).